(untitled) (Al-Mansour Journal, 2025)
With the ever-growing demand for ultra-low-latency communication in Vehicle-to-Everything (V2X), traditional software-based approaches to encryption have become an increasingly challenging subject. We propose the current adaptive encryption architecture in FPGA to enhance the real-time functionality of vehicular networks in 5G and beyond. Through the parallelism and reconfigurability properties of FPGAs, the proposed model dynamically alters cipher algorithms and key scheduling based on message priority and network situation. A modular encryption core, real-time key scheduler, and stream/block controller are developed on a Xilinx Zynq-7000 System-on-Chip (SoC)for fast and flexible cryptographic processing. Experimental performance in a simulated V2X traffic demonstrates a 42% decrease in latency and 36% increase in throughput with respect to standard microcontroller solutions, in full conformance to European Telecommunications Standards Institute Intelligent Transport Systems - G5 (ETSI ITS-G5) and 3GPP V2X. It also takes advantage of runtime cipher reconfiguration and is resistant to timing side-channel and replay attacks. These findings emphasize the feasibility of the proposed approach for secure deployment in the emerging intelligent transportation systems.